Family Support for Psychological Health of the Elderly - Mierrina; Pradana , Charis Rizqi; Rahmawati, Haniyah Dwi (Proceedings of International Conference on Da'wa and Communication, 2021)
With the increasing number of elderly people, of course, there will be more and more complex problems that must be faced by these elderly people. Elderly people are no longer independent or dependent on others, unable to carry out activities on their own, need caregivers, have cognitive and functional decline, have complex psychosocial problems, and have multiple diseases. This study aims to provide an overview of the form of support and its impact on the health of the elderly by providing an overview through literature review research. Research data was obtained through literature study and hermeneutics. Family support can provide great hope for elderly people to continue to instill many positive things and reduce the negative possibilities experienced by them. Ways to provide support to the elderly can be: taking family members for walks, hanging out with friends, being with them throughout the day, and respecting one another. The benefits of providing the above are that there is an increasingly close family relationship, trusted by elderly parents, to be asked for any help, not awkward in expressing any opinion. This has an impact on the emotional stability of the elderly in living their lives.